ASSOCIATION OF SERUM FOLIC ACID LEVELS AND CHOLESTEROL/HIGH DENSITY LIPOPROTEIN (HDL) RATIO WITH BASAL METABOLIC INDEX (BMI) IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION - Siddique, Nimrah; Cheema, Rabia Akhtar; Latif, Javaria; Waseem, Uzma; Altaf, Muhammad Omer; Aslam, Saeed (Pakistan Armed Forces Medical Journal, 2021)
Objective: Different lipid profile markers have been used recently in making the prognosis of acute myocardial Infarction Patients. Cholesterol-high density lipoprotein ratios and serum folic acid levels were compared with basal metabolic index (BMI) status in patients with acute myocardial infarction in this study.Study Design: Cross-sectional study.Place and Duration of Study: University of Health Sciences Lahore, from Oct 2017 to Oct 2018.Methodology: Study approval from Advanced Studies and Research Board of University of Health Sciences Lahore. A validated questionnaire was filled by the patients after taking informed consent from them. Convenient sampling technique was used. Blood samples of the patients were also taken to calculate different parameters.Results: The mean age of the patients included in the study was 52.31 years. Majority were males (85%). More than half were having no formal education (55%). Majority also belonged to middle class as per their socio-economic status (57.5%). About 50% were within normal weight category and 20% were in over weight category. Mean basal metabolic index of the study participants was found to be 25.32. We also calculated the association of serum folic acid levels with different groups of basal metabolic index. Among underweight study participants the mean folic acid levels were found to be very low (3.86ng/mlnormal is 6-17ng/ml). The result was also found to be statistically non-significant. When the association of basal metabolic index was assessed with cholesterol/HDL ratio, it was found to be highly statistically significant (p=0.047). The ratio was also seen to be decreased with....................